Hadith #2255 - Sunan Abi Dawud - Aabad bin Mnswr عباد بن منصور; al-Hasan bin 'Ali al-Halwani الحسن بن علي الخلال الحلواني; ibn Abbas; Ikrama عكرمة; Yazid bin Harun يزيد بن هارون (Sunan Abi Dawud)
When the Prophet (ﷺ) ordered a man and his wife to invoke curses on each other, he ordered a man to put his hand on his mouth when he came to the fifth utterance, saying that it would be the deciding one.
Grade: Sahih